Indonesian senior high school students’ fear of negative evaluation: Relationship with L2 speaking self-efficacy - Adaninggar Septi Subekti; Christina Helen Indarto (Englisia: Journal of Language, Education, and Humanities, 2026)
Research examining the relationship between Fear of Negative Evaluation (FNE)-a well-documented anxiety construct originating in social psychology-and second/foreign language (L2) speaking self-efficacy (SSE) remains limited, particularly within the Indonesian educational context, and especially among secondary school populations. To address this empirical gap, the present study was designed with two primary aims: first, to investigate the levels of FNE experienced by Indonesian high school students in English language classrooms, and second, to determine the extent to which FNE statistically predicts their L2 SSE. A paper-based survey was administered to a sample of 160 students enrolled at a private high school in Yogyakarta, Indonesia. Descriptive statistical analyses indicated that participants’ FNE levels ranged from moderate to high. Notably, FNE associated with peers was generally more pronounced than FNE specifically tied to classroom activities or English performance, suggesting that social evaluative concerns are particularly salient among this population. The results further revealed that students' L2 SSE fell within the low-to-moderate range, indicating limited confidence in their English-speaking abilities. Bivariate regression analysis demonstrated that FNE accounted for 18.4% of the total variance in L2 SSE, a statistically meaningful proportion, while the remaining 81.6% was attributable to factors external to the model, such as prior language achievement, teacher feedback, and individual differences. These findings carry several pedagogical implications, including the importance of cultivating a supportive classroom climate, fostering peer encouragement, and promoting positive group dynamics to mitigate students’ FNE and enhance their L2 speaking self-efficacy.